THE PUBLIC ACCOUNTANT OF TODAY AND TOMORROW. - Quenan, John W. (The Accounting Review, 1946)
This article says that accounting and accountants had their beginning in bookkeeping and bookkeepers. Modern bookkeeping apparently first came into general usage in the fifteenth century in response to the rapidly growing commerce and trade conducted by proprietorships and partnerships in the Italian republics. The bookkeeping of that time, although basically the same as present-day bookkeeping, was very simple, as suited the needs of business, and was based on a few simple rules of debit and credit and recording procedure. Theory and accountants did not exist, it was necessary only that bookkeepers of the time be accurate, methodical, and attentive to application of the rules. Although the profession of accounting, even in its early days, included among its members many men with broad liberal education, mans' of its members for the first quarter of the twentieth century were self-taught as to the technical aspects of their profession. With the growth of large corporations and the increasing intricacies of corporate accounting, the larger corporations found that the accounting problems incident to their operations required employees, such as comptrollers, auditors, and treasurers, with a higher type of training and education than the bookkeeper.